Mobility hubs in the context of urban logistics – a proposal for Lodz - Królikiewicz, Bartosz (Contemporary challenges of transport, freight forwarding and logistics - selected aspects, 2023)
Based on the survey, the authors drew conclusions about transportation preferences, attitudes to the "Fit for 55" document, necessary conditions for abandoning individual vehicles in favor of public transportation, or opinions on the creation of mobility hub in the city of Lodz. Reference was also made to the method of emotional maps of the city to consider the possible locations of such solutions, based on the assumption that places that are particularly liked and frequently frequented are those where such solutions could be created. The theoretical context of the considerations is city logistics, within which solutions are proposed to level the transportation problems of cities, which are pricing tools, infrastructural or organizational changes in cities.